2019
DOI: 10.3390/en12224377
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations on the Inner Flow Behavior of Centrifugal Pumps under Inlet Air-Water Two-Phase Conditions

Abstract: Centrifugal pumps are widely used and are known to be sensitive to inlet air-water two-phase flow conditions. The pump performance degradation mainly depends on the changes in the two-phase flow behavior inside the pump. In the present paper, experimental overall pump performance tests were performed for two different rotational speeds and several inlet air void fractions (αi) up to pump shut-off condition. Visualizations were also performed on the flow patterns of a whole impeller passage and the volute tongu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…Inside the volute channel, the air with high air content is mainly distributed far from the impeller. Around the tongue area, the air with high air content is mainly distributed away from the tongue and finally flows to the outlet pipe, which is consistent with the flow pattern distribution observed in the literature [5]. Figure 19 shows the location of eight volute sections.…”
Section: Flow Inside the Impeller And Volute Sectionsupporting
confidence: 85%
See 1 more Smart Citation
“…Inside the volute channel, the air with high air content is mainly distributed far from the impeller. Around the tongue area, the air with high air content is mainly distributed away from the tongue and finally flows to the outlet pipe, which is consistent with the flow pattern distribution observed in the literature [5]. Figure 19 shows the location of eight volute sections.…”
Section: Flow Inside the Impeller And Volute Sectionsupporting
confidence: 85%
“…Some physical explanation about performance improvements on handing maximum acceptable inlet two phase void fractions capability of centrifugal pumps are given.Energies 2020, 13, 65 2 of 25 of the flow pattern. The pump performance degrades as the α 0 increase and generates undesired pulsation problems, endangering the operation stability and reliability of the system [4,5]. Therefore, it is especially important to thoroughly study and reveal the internal flow characteristic of centrifugal pumps under gas entrainment conditions.…”
mentioning
confidence: 99%
“…In addition, the rotational speed does not really have any effect on the empirical models for the prediction of both pump performance and surging mechanism. However, the actual pump performance analyses on our two data sets [46] (Table 4) have shown that the performance degradation of the pump running at lower rotational speeds (1000 rpm) was worse compared to higher rotational speeds (1450 rpm). Furthermore, our study has proved that the rotational speed is an important parameter that permits the pump to work better when handling multiphase flow conditions.…”
Section: Study Empirical Correlation Related Parametersmentioning
confidence: 88%
“…Since then, many researchers, such as Patel [49], Kim [50], Furukawa [51], Sato [52], Andras [53], Takemura [54], Estevam [10], Thum [55], Izturitz [56], Barrios [3,17], Schafer [57,58], Shao [59], Si [46], Cubas [60], have put their efforts towards flow visualization, in order to achieve complete information about bubble behavior within impeller and gaspocket formation. Among these, Patel [49], Kim [50], and Takemura [54], Sato [52], and Thum [55] have discussed, in detail, the bubble agglomeration mechanism where Patel [49] and Kim [50] explained that the accumulation of the bubbles happens due to strong slippage effect between the liquid and gas phase which cannot be ignored inside the impeller flow channel.…”
Section: Flow Visualization and Bubble Size Measurementmentioning
confidence: 99%
See 1 more Smart Citation